JAK2 variations and functions in lung adenocarcinoma - Yanjun Xu; Juan Jin; Jiawei Xu; Yang W Shao; Yun Fan (Tumor Biology)
Lung cancer ranks as the first most common cancer and the first leading cause of cancer-related death in China and worldwide. Due to the difficulty in early diagnosis and the onset of cancer metastasis, the 5-year survival rate of lung cancer remains low. JAK2 has emerged as pivotal participant in biological processes, often dysregulated in a range of cancers. Recently our study found that JAK2 might play an important role in lung cancer pathogenesis. While our understanding of JAK2 in the onset and progression of lung cancer is still in its infancy, there is no doubt that understanding the variations and functions of JAK2 will certainly secure strong biomarkers and improve treatment options for lung cancer patients. The expression level of JAK2 mRNA was assayed using RT-PCR. JAK2 mutations and amplification were detected using next-generation sequencing (NGS). The shRNA and overexpression plasmids of JAK2 were conducted. MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazoliumbromide) assay, Trans-well migration and Matrigel invasion assay were conducted to study the proliferation, migration and invasion abilities of lung adenocarcinoma cells independently. We found that JAK2 mRNA was up-regulated in lung adenocarcinoma tissues when compared with their adjacent non-tumor tissues, and was associated with lymph node metastasis ( p < 0.05). JAK2 V617F and N30S mutations and JAK2 amplification were detected by NGS in plasmid samples in patients with lung adenocarcinoma. Downregulation of JAK2 inhibited the proliferation, migration and invasion abilities of lung adenocarcinoma A549 cells. Moreover, overexpression of JAK2 induced the proliferation, migration and invasion abilities of A549 cells. Thus, the up-regulation, mutation and amplification of JAK2 detected in lung adenocarcinoma may participate in lung cancer progression by regulating cancer cells’ proliferation, migration and invasion.